1977
DOI: 10.1063/1.89218
|View full text |Cite
|
Sign up to set email alerts
|

Chirped-grating demultiplexers in dielectric waveguides

Abstract: A wavelength-selective beamsplitter has been realized by fabricating chirped (variable period) grating in an optical waveguide. This beamsplitter can demultiplex a signal traveling in a fiber and send each frequency component to a different fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…Passive components such as corrugated grating structures have wide applicability in modern optical devices such as distributed feedback (DFB) lasers (Wang 1974), Bragg reflector (DBR) lasers (Wang 1974), wavelength filters (Flanders et al 1974), input and output couplers, multiplexers (Livanos et al 1977), in switch structures (Srivastava et al 2008) etc. Analysis of first order Bragg gratings show that there is large wavelength discrimination.…”
Section: Corrugated Structuresmentioning
confidence: 99%
“…Passive components such as corrugated grating structures have wide applicability in modern optical devices such as distributed feedback (DFB) lasers (Wang 1974), Bragg reflector (DBR) lasers (Wang 1974), wavelength filters (Flanders et al 1974), input and output couplers, multiplexers (Livanos et al 1977), in switch structures (Srivastava et al 2008) etc. Analysis of first order Bragg gratings show that there is large wavelength discrimination.…”
Section: Corrugated Structuresmentioning
confidence: 99%
“…From all the curves it is apparent that the same deviations of beam 1 and 2 from the corresponding Bragg angles produce different changes of position and spatial frequency in the interference pattern . From the theoretical point of view this is a consequence of the non-linear functions in equations (15) and (16) . Figures 13 and 14 illustrate the experimental dependence on cp of a and AG in the observation plane (x, y)-plane .…”
Section: Downloaded By [George Mason University] At 15:26 29 Decembermentioning
confidence: 95%
“…HOEs formed by recording the interference pattern of non-plane coherent light beams, so-called chirped or curved-line gratings, can be used for imaging purposes in optical circuits [13][14][15] and as multiplexer and . demultiplexer [16] . In integrated optical circuits, HOEs can also find a wide application as active devices like modulators and deflectors [17] .…”
Section: Introductionmentioning
confidence: 99%
“…In the Appendix it is shown that the continuity of E and H z follows directly from the continuity of E, Ey, Hx, Hy and thus does not give a new set of equations. The requirement of the continuity of the tangential field components over the whole 1-2 boundary leads to this set of four equations, (3 …”
Section: Mode-matching Proceduresmentioning
confidence: 99%
“…The phenomenon is observed in strip waveguides, slab waveguide edges, thin film lenses and prisms, modulators with a buffer layer under the electrodes, gratings, etc. However, surface relief gratings are widely used as input-output couplers [1], reflectors for semiconductor lasers [2], demultiplexers and filters [3,4] and phase-matching elements [5].…”
Section: Introductionmentioning
confidence: 99%